Improving the technology of producing food grade dye from red beet juice - Melnyk, Lyudmila; Sheiko, Tamila; Stroy, A. (My University, 2012)
Red beet juice is very useful food product, because it contains significant amount of sugars, mineral substances and vitamins. It is also valuable because it is used for producing food grade dye. Nowadays in order to give to food products a color, close to natural coloring of fruits and vegetables, expensive synthetic dyes are used, which might have cancer-inducing effect when being accumulated by human organism. The refore improving the technology for producing food grade dye from red beet juice is remarkably important task. Currently for the purpose of obtaining dye from red beet juice, a part of pectin substances,which make the process of juice concentration more difficult, is removed with the help of expensive enzymatic agents. The authors have suggested using natural carbon-bearing adsorbent shungite to purify red beet juice from pectin substances.
Keywords: food grade dye; shungite; red beet juice; natural adsorbent; харчовий барвник; шунгіт; сік червоного буряка; природний адсорбент; пищевой краситель; шунгит; сок красной свеклы; природный адсорбент; кафедра процесів і апаратів харчових виробництв